Switch-2 determines Mg2+ADP-release kinetics and fine-tunes the duty ratio of Dictyostelium class-1 myosins - Diensthuber, Ralph P.; Hartmann, Falk K.; Kathmann, Daniela; Franz, Peter; Tsiavaliaris, Georgios (Frontiers in Physiology, 2024)
Though myosins share a structurally conserved motor domain, single amino acid variations of active site elements, including the P-loop, switch-1 and switch-2, which act as nucleotide sensors, can substantially determine the kinetic signature of a myosin, i.e. to either perform fast movement or enable long-range transport and tension generation. Switch-2 essentially contributes to the ATP hydrolysis reaction and determines product release. With few exceptions, class-1 myosin harbor a tyrosine in the switch-2 consensus sequence DIYGFE, at a position where class-2 myosins and a selection of myosins from other classes have a substitution. Here, we addressed the role of the tyrosine in switch-2 of class-1 myosins as potential determinant of the duty ratio. We generated constitutively active motor domain constructs of two class-1 myosins from the social amoeba D. discoideum, namely Myo1E, a high duty ratio myosin and Myo1B, a low duty ratio myosin. In Myo1E we introduced mutation Y388F and in Myo1B mutation F387Y. The detailed functional characterization by steady-state and transient kinetic experiments, combined with in vitro motility and landing assays revealed an almost reciprocal relationship of a number of critical kinetic parameters and equilibrium constants between wild-type and mutants that dictate the lifetime of the strongly actin-attached states of myosin. The Y-to-F mutation increased the duty ratio of Moy1B by almost one order of magnitude, while the introduction of the phenylalanine in switch-2 of Myo1E transformed the myosin into a low duty ratio motor. These data together with structural considerations propose a role of switch-2 in fine-tuning ADP release through a mechanism, where the class-specific tyrosine together with surrounding residues contributes to the coordination of Mg 2+ and ADP. Our results highlight the importance of conserved switch-2 residues in class-1 myosins for efficient chemo-mechanical coupling, revealing that switch-2 is important to adjust the duty ratio of the amoeboid class-1 myosins for performing movement, transport or gating functions.